The Role of Islamic Education in Promoting Peace and Tolerance - Dr. Muhammad Riaz; Fehmida Baloch; Mahreen Siddiqui; Rida Ejaz; Mukhtar Bashir (Al-Qanṭara, 2023)
This study provides a concise overview of the study's focus on the role of Islamic education in fostering peace and tolerance. In an increasingly interconnected world marked by diverse cultures and belief systems, the need for peaceful coexistence and interfaith understanding is paramount. This study examines how Islamic education, rooted in the teachings of the Quran and the life of Prophet Muhammad, can serve as a catalyst for promoting peace and tolerance both within Muslim communities and in the broader global context. The research delves into the core principles of Islam that emphasize compassion, justice, and respect for the dignity of all human beings. It explores how Islamic educational institutions, such as madrasas and schools, play a pivotal role in shaping the values and worldviews of Muslim youth. Furthermore, the study investigates the curricula, pedagogical approaches, and extracurricular activities that contribute to nurturing a mindset of tolerance and peaceful coexistence. Through a comprehensive review of literature, case studies, and interviews with educators and religious leaders, this research seeks to identify best practices and challenges in incorporating peace and tolerance education within Islamic educational frameworks. It highlights examples of successful initiatives and innovative methods employed by educational institutions to instill the values of empathy, dialogue, and reconciliation among students. The study also acknowledges the potential impact of technology and social media in amplifying messages of peace and tolerance from within the Muslim community. It explores the role of Islamic scholars, imams, and community leaders in disseminating these values and countering extremist ideologies. Ultimately, this research aims to contribute to the ongoing discourse on interfaith dialogue and global peacebuilding. By recognizing the positive role that Islamic education can play in nurturing individuals who are committed to peace and tolerance, it provides insights into strategies for promoting harmony and understanding among people of different faiths and backgrounds in an increasingly diverse world.